2011
DOI: 10.1002/chin.201202275
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Unitary Quantum Theory and Catalytic Process Theory

Abstract: Review: 27 refs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(44 citation statements)
references
References 6 publications
0
44
0
Order By: Relevance
“…In Unitary Quantum Theory a particle is described as a wave packet that in its movement is periodically spreading along the Metagalaxy and is gathering again. For such moving wave packet both the relativistic and the classical mechanics follow from these unitary quantum equations, probably the Maxwell equations and the gravitation follow from exact UQT equations [8,[13][14][15], but this has not been proved yet being the problem of the future. Nevertheless the UQT scalar equation (a telegraph type) in general makes it possible to obtain not only Schrödinger but also Maxwell equations [14,15].…”
Section: Consider Relativistic Quantum Field Theory and Electrodynamimentioning
confidence: 99%
See 1 more Smart Citation
“…In Unitary Quantum Theory a particle is described as a wave packet that in its movement is periodically spreading along the Metagalaxy and is gathering again. For such moving wave packet both the relativistic and the classical mechanics follow from these unitary quantum equations, probably the Maxwell equations and the gravitation follow from exact UQT equations [8,[13][14][15], but this has not been proved yet being the problem of the future. Nevertheless the UQT scalar equation (a telegraph type) in general makes it possible to obtain not only Schrödinger but also Maxwell equations [14,15].…”
Section: Consider Relativistic Quantum Field Theory and Electrodynamimentioning
confidence: 99%
“…For such moving wave packet both the relativistic and the classical mechanics follow from these unitary quantum equations, probably the Maxwell equations and the gravitation follow from exact UQT equations [8,[13][14][15], but this has not been proved yet being the problem of the future. Nevertheless the UQT scalar equation (a telegraph type) in general makes it possible to obtain not only Schrödinger but also Maxwell equations [14,15]. The field of investigations of the Unified Unitary Quantum Theory (UUQT) is the most profound level of substance: the level of elementary particles and quantum effects.…”
Section: Consider Relativistic Quantum Field Theory and Electrodynamimentioning
confidence: 99%
“…However, (Sapogin et al, 2003(Sapogin et al, , 2005(Sapogin et al, , 2008a an interesting was found for a modified scalar version of the integro-differential Equation (30), which may be written down as follows:…”
Section: A Modified Scalar Version Of the Integro-differential Equationmentioning
confidence: 99%
“…Calculation spectrum masses some elementary particles see (Sapogin et al, 2008a(Sapogin et al, , 2008b(Sapogin et al, , 2010.…”
Section: Calculation Of Dimensionless Electrical Charge and The Valuementioning
confidence: 99%
See 1 more Smart Citation